Primary Hepatic Osteosarcoma: A Rare Case Report - Janaki, Amutha; A, Kavitha; P, Sindhura (Annals of Pathology and Laboratory Medicine, 2019)
Primary Hepatic Osteosarcoma is a very rare tumor with very few literatures available till date. We report a case of 61 year old male presented with abdominal pain and distention. MRI/CT showed a large heterogenous lesion in the liver, which turned out to be primary hepatic osteosarcoma, and confirmed using Immunohistochemistry, after ruling out metastatic deposits